2018
DOI: 10.1016/j.bioelechem.2018.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Growth and current production of mixed culture anodic biofilms remain unaffected by sub-microscale surface roughness

Abstract: Bioelectrochemical systems couple electricity demand/supply to the metabolic redox reactions of microorganisms. Generally, electrodes act not only as electron acceptors/donors, but also as physical support for an electroactive biofilm. The microorganism-electrode interface can be modified by changing the chemical and/or topographical features of the electrode surface. Thus far, studies have reported conflicting results on the impact of the electrode surface roughness on the growth and current production of bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 41 publications
1
10
1
Order By: Relevance
“…However, recent studies have shown that although structurest hat are small compared to the biofilm thickness can influence biofilm attachment and initial growth,t hey do not significantly enhance long-term performance. [19][20][21] Macrostructures with ac omparatively larger size [22] can, however,d rastically increaset he current density,w hichh as been shown by several studies with specific 3D macrostructure designs. [15,17,23] Here, clogging of the 3D structures during the biofilm growth represents a major obstacle that needs to be overcome.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…However, recent studies have shown that although structurest hat are small compared to the biofilm thickness can influence biofilm attachment and initial growth,t hey do not significantly enhance long-term performance. [19][20][21] Macrostructures with ac omparatively larger size [22] can, however,d rastically increaset he current density,w hichh as been shown by several studies with specific 3D macrostructure designs. [15,17,23] Here, clogging of the 3D structures during the biofilm growth represents a major obstacle that needs to be overcome.…”
Section: Introductionmentioning
confidence: 95%
“…The introduction of small structures (i.e., nanometer or micrometer scale) can drastically increase the electrochemically active surface area of an electrode. However, recent studies have shown that although structures that are small compared to the biofilm thickness can influence biofilm attachment and initial growth, they do not significantly enhance long‐term performance . Macrostructures with a comparatively larger size can, however, drastically increase the current density, which has been shown by several studies with specific 3 D macrostructure designs .…”
Section: Introductionmentioning
confidence: 99%
“…Especially, the core element bioanode is in the focus of research and development. Independent from the electrode material, chemical and physical modifications have been applied successfully to increase electrode performances in BES (He et al, 2011;Guo et al, 2013;Kipf et al, 2013;Artyushkova et al, 2015;Baudler et al, 2015;Champigneux et al, 2018;Pierra et al, 2018;Moß et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…According to our analysis the cAD1 precursor and its orthologs from other bacteria are encoded by genes adjacent to apbE homologs (Figure 2-Figure 5). A number of mentioned above Firmicutes genera [32], [33] and particularly Listeria [34], Catonella [35] representatives, as well as Bacteroidia (Bacteroides) [36], were considered as electrogenic and shown to populate MFCs [4] under different conditions. We show that cAD1 precursor has two sites specific for ApbE-dependent FMN insertion (TGAT) ( Figure 7), and its homologs have at least one FMN covalent binding insertion motif.…”
Section: Discussionmentioning
confidence: 99%